La formación en psicooncología - Cruzado, Juan A. (Psicooncología, 2003)
In the present article, Psycho-oncology is defined as an interdisciplinary field of psychology and biomedical sciences aimed to cancer etiology, prevention, diagnosis, assessment, treatment, rehabilitation and palliative care, as well as the improvement of health professionals ´ interaction and communication skills, besides the optimization of resources to promote the efficacy and quality of oncological services. It is also proposed a training program in Psychooncology, which includes the programme description, aims, methods, students selection criteria, assessment methods and quality evaluation. This training program is focused on the following areas: a) clinical issues of cancer, b) organization of atentional services, c) bioethics, deontology and legal aspects, d) psychological and social factors involved, e) clinical and health assessment, f) psychopathology, g) treatments, h) health promotion programs, prevention, early detection and genetic counseling, i) multiprofessional team and burnout prevention and j) research methodology. It is emphasized the need to promote more research on Psycho-oncology treatment outcomes and to include in the training program the procedures and treatment techniques that have been empirically supported, based on the 12 division of APA criteria (Task Force).